Odpowiedzi

2010-01-19T17:52:24+01:00
A) 2a + 3b - c - 4a - 3b + 2c =-2a+c
b) 3x - 2y + 3,5x - y + 2 + 0,5y =6,5x-2,5y+2
c) xy + 3x - y +1 - 2xy - 2x + y + 1 =x-xy+2
d) x²+ 2xy-3y ² -2x ² - y²- x ²+ 2xy =-2x^-4y^+4xy
3 2 3
2010-01-19T17:53:47+01:00
A) 2a + 3b - c - 4a - 3b + 2c =-2a+c

b) 3x - 2y + 3,5x - y + 2 + 0,5y =6,5x-2,5y+2

c) xy + 3x - y +1 - 2xy - 2x + y + 1 =-xy+x+2+y

d) x²+ 2xy-3y ² -2x ² - y²- x ²+ 2xy =-2x²+4xy-4y²

:P
6 3 6
2010-01-19T17:55:32+01:00
A) 2a + 3b - c - 4a - 3b + 2c = 2a+c ---> -3b z +3b się skraca

b) 3x - 2y + 3,5x - y + 2 + 0,5y =6,5x - 2,5y +2

c) xy + 3x - y +1 - 2xy - 2x + y + 1 = -xy + x +2----> -y z +y się skraca
+1 z -1 się skraca

d) x²+ 2xy-3y ² -2x ² - y²- x ²+ 2xy =
- 2x(kwadrat) + 4xy -4y(kwadrat)
1 1 1